A new pragmatic approach to solve the problems of vector optimization with uncertain parameters; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Reizlin (Reyzlin) V. I. Valery Izrailevich (Numerical Simulation of Applied Problems, 2016)
Title screen